Coming Late for Dinner: Localized Digestate Depot Fertilization for Extensive Cultivation of Marginal Soil With Sida hermaphrodita - Nabel, Moritz; Schrey, Silvia D.; Poorter, Hendrik; Koller, Robert; Nagel, Kerstin A.; Temperton, Vicky M.; Dietrich, Charlotte C.; Briese, Christoph; Jablonowski, Nicolai D. (Frontiers in Plant Science, 2018)
Improving fertility of marginal soils for the sustainable production of biomass is a strategy for reducing land use conflicts between food and energy crops. Digestates can be used as fertilizer and for soil amelioration. In order to promote plant growth and reduce potential adverse effects on roots because of broadcast digestate fertilization, we propose to apply local digestate depots placed into the rhizosphere. We grew Sida hermaphrodita in large mesocosms outdoors for three growing seasons and in rhizotrons in the greenhouse for three months both filled with marginal substrate, including multiple sampling dates. We compared digestate broadcast application with digestate depot fertilization and a mineral fertilizer control. We show that depot fertilization promotes a deep reaching root system of S. hermaphrodita seedlings followed by the formation of a dense root cluster around the depot-fertilized zone, resulting in a five-fold increased biomass yield. Temporal adverse effects on root growth were linked to high initial concentrations of ammonium and nitrite in the rhizosphere in either fertilizer application, followed by a high biomass increase after its microbial conversion to nitrate. We conclude that digestate depot fertilization can contribute to an improved cultivation of perennial energy-crops on marginal soils.